Alignment between data warehouse design and business strategy - Mior Nazri, Mior Nasir; Hamid, Zarinah (Institute of Information System & Research Center, 2015)
Data warehouse has become a very important tool for supporting the corporate executives in making important decisions in a highly competitive business environment. Data warehouse enables the top management to acquire and analyze integrated data extracted globally across the enterprise. Many organizations are sitting on vast amount of data already accumulated in their operational database. The huge data repository with potential strategic business information can be analysed comprehensively only through the usage of data warehouse system. The main objective of this paper is to systematically review the development and adoption of data warehouse design in business environment and the different models to assess the alignment between information technology strategy and business strategy.